Bremsstrahlung production from 10–30 MeV electrons incident on thick targets: Monte Carlo simulation with penelope. (July 2023) - García-Higueras, P.A.; García-Pareja, S.; Salvat, F.; Lallena, A.M.
Abstract: Purpose: : To study the effect of the user-defined electron/positron simulation parameters C 1 and C 2 of the Monte Carlo code penelope on the results from simulations of bremsstrahlung photons generated by high energy electrons incident on thick targets. Methods: The version 2018 of the code system penelope, with four different sets of simulation parameters, is used to calculate the photon fluences produced by electron beams with initial energies ranging between 10 and 30 MeV impinging on thick elemental targets of Be, Al and Pb. Using the calculated fluences, the integrated photon yields and the mean energies of the detected photons are also evaluated. The Monte Carlo results are compared to the available experimental data, the comparison being quantified by means of χ 2 statistics. Results: Although acceptable agreement of simulation results with experimental data is found for all the simulations performed, a significant improvement in this agreement is observed when the parameter values C 1 = C 2 = 0 . 01 or 0.001 are used, that is, when the simulations are more detailed. In the case of the mean energy of the detected photons, similar results are obtained in all the simulations. The results obtained with this version of the code improve those found with older versions in case of the Pb target. Conclusions: Regarding the emission of bremsstrahlung photons by MeV electrons, simulations with C 1 = C 2 = 0 . 01 produce results that approximate the experimental data equally well as more detailed simulations with C 1 = C 2 = 0 . 001, with a reduction of the simulation time between 81% and 89%, depending on the initial energy of the electrons. Highlights: Bremsstrahlung emission by MeV electrons is simulated with the penelope code. Simulated photon fluences, yields and mean energies are compared to experimental data. Electron beams with 10 to 30 MeV and detection angles from 0 to 90°are considered. The parameters C1 and C2 should not be larger than 0.01 to describe the data. No significant improvement is found with C1 and C2 smaller than 0.01.